Denitrification using excess activated sludge as carbon source: Performance and the microbial community dynamics. (August 2017) - Sun, Haohao; Wu, Qiang; Yu, Ping; Zhang, Liangying; Ye, Lin; Zhang, Xu-Xiang; Ren, Hongqiang
Highlights: The excess activated sludge was successfully used as denitrification carbon source. The NO3 − -N in effluent wastewater from WWTP can be reduced down to <1 mg/L. Pseudomonas and Thauera may easily release organic matters for the denitrification. Abstract: In this study, the feasibility of using excess activated sludge as carbon source for denitrification to remove low concentrations of nitrate from wastewater was investigated. With an optimized upflow anaerobic reactor, high denitrification performance for both synthetic wastewater and effluent from municipal wastewater treatment plant was achieved. The results showed that the nitrate nitrogen can be reduced down to <1 mg L −1 with a hydraulic retention time of 6 h. The total nitrogen removal increased with the amount of sludge added, while, the nitrogen removal per unit of added sludge decreased with the amount of sludge added. 16S rRNA gene high-throughput sequencing showed that the bacterial community changed during the startup period and the subsequent denitrification process. And, it was found that some bacterial species in genus Pseudomonas and Thauera obviously decreased during the reactor operation, suggesting that they were likely digested and released organic matters for the denitrification.